Pediatric prevention from the perspective of parents of children up to two years old - Salwa, Agata Anna (Journal of Education, Health and Sport, 2018)
Background: During the first years of life, the child should be under the constant supervision of a specialist who will follow and supervise the proper development of the new organism. Systematic visits at the pediatrician will allow the doctor to see any developmental disorders, correct irregularities, carry out vaccinations in time, and help parents determine the principles of feeding and nursing the child, so as to strengthen his immunity. Each visit to the pediatrician should include a full medical examination, assessment of physical development (measurement of weight and height, as well as head circumference) and evaluation of psychomotor development. Materials & Methods: In this work the method of diagnostic survey was used. The research used a survey technique. The tool used in conducting the research was a questionnaire, which contained 20 closed, one-time and multiple-choice questions. The first part of the questionnaire is a questionnaire, which contains general questions pertaining to: age, sex, education and place of residence. The second part of the questionnaire included questions about primary care, compliance with the calendar of preventive visits, expectations of the doctor and other medical staff as well as the availability of specialists as well as reasons for changing primary and private medical care. Results & Conclusion: The goal of preventive care is to ensure health and a good start in the life of as many children as possible. Parents and medical staff of basic health care should be partners. In the exercise of this care, which would be manifested in mutual understanding, support and cooperation for health and development of children. Mutual trust and good communication are an indispensable condition for catching emerging threats, as well as possible errors of each party. Cooperation and partnership should result in increased support of the care system for parents and vice versa for the medical staff, but also a greater level of mutual control. Effective cooperation requires understanding, which is why primary health care should adapt the methods of communication to the needs and specificity of the new generation of parents.